2019
DOI: 10.1172/jci123106
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial miR-30c suppresses tumor growth via inhibition of TGF-β–induced Serpine1

Abstract: Conflict of interest: DGA has applied for a patent on 7C1 entitled "Conjugated lipomers and uses thereof" (US patent application no. 9238716).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 78 publications
3
60
0
Order By: Relevance
“…It has been found that miR-30c was low expressed in breast cancer [31], prostate cancer [32], colon cancer [33], medulloblastoma [34], as well as lung cancer [35], gastric cancer [36]and multiple myeloma [37], compared with these corresponding adjacent tissues. Increasing research shows miR-30c can be regulated or mutated by oncogenic transcription factors and cancer-associated genes.…”
Section: The Function Of Mir-30c In Cancer Progressionmentioning
confidence: 99%
“…It has been found that miR-30c was low expressed in breast cancer [31], prostate cancer [32], colon cancer [33], medulloblastoma [34], as well as lung cancer [35], gastric cancer [36]and multiple myeloma [37], compared with these corresponding adjacent tissues. Increasing research shows miR-30c can be regulated or mutated by oncogenic transcription factors and cancer-associated genes.…”
Section: The Function Of Mir-30c In Cancer Progressionmentioning
confidence: 99%
“…Immune infiltrating cells induce wound-like inflammation in the tumor microenvironment, further assisting in the development of malignant cancers. Poor perfusion of solid tumors leads to high levels of hypoxia and low metabolite availability, and the healing response responds to these via angiogenesis [7,8]. Leaky vasculature results in high osmolarity in the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…EBV was associated with B lymphoma such as Burkitt, Hodgkin and Diffuse Large B cell Lymphomas (DLBCL) [3]. The expression of miR-30c was positively correlated to survival of breast cancer patients [38,39]. Loss of miR-424 was associated with aggressiveness of breast cancers in human.…”
Section: Circrnaome Of Ebv Sponged Mirnas Of Host Cells Involved In Mmentioning
confidence: 99%